2017
DOI: 10.1016/j.ophtha.2016.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Associations with Retinal Pigment Epithelium Thickness Measures in a Large Cohort

Abstract: We describe novel findings of RPE-BM thickness in normal individuals, a structure that varies with age, ethnicity, refraction, IOP, and smoking. The significant association with IOP is especially interesting and may have relevance for the etiology of glaucoma, while the association between age and smoking may have relevance for the etiology of age-related macular degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 23 publications
5
52
0
Order By: Relevance
“…In another part of the UK Biobank study, Ko and colleagues reported that the mean retinal pigment epithelium-Bruch´s membrane thickness (26.3 ± 4.8 μm) in the central subfield showed an agerelated thinning after an age of 45 years. 31 The findings obtained in our study suggest that the ageing process affected all retinal layers in all regions of the macula. These results were supported by the findings obtained in histological studies in which 0.3% to 0.6% of the retinal ganglion cells and retinal ganglion cell axons, 0.2% of the photoreceptor cones, 0.4% of the photoreceptor rods and 0.3% of the RPE cells were lost per year.…”
Section: Discussionsupporting
confidence: 56%
“…In another part of the UK Biobank study, Ko and colleagues reported that the mean retinal pigment epithelium-Bruch´s membrane thickness (26.3 ± 4.8 μm) in the central subfield showed an agerelated thinning after an age of 45 years. 31 The findings obtained in our study suggest that the ageing process affected all retinal layers in all regions of the macula. These results were supported by the findings obtained in histological studies in which 0.3% to 0.6% of the retinal ganglion cells and retinal ganglion cell axons, 0.2% of the photoreceptor cones, 0.4% of the photoreceptor rods and 0.3% of the RPE cells were lost per year.…”
Section: Discussionsupporting
confidence: 56%
“…GA is likely a consequence of the general RPE thinning occurring with advancing age as shown in a large cohort of about 70,000 individuals in the UK Biobank study. 22 The ancillary OCT-AREDS study indicated a 32% increase to the odds of developing GA for every 0.001 mm 3 increase in abnormal thinning of the RPE-drusen complex, offering a composite marker of drusen regression with RPE atrophy. 20 The literature regarding risk factors for GA is richer than that for CNV, and the results are more consistent.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in line with our observations in humans in vivo . The RPE-BM complex does not seem to increase outside of the foveal minimum and there may even be a decrease with age in the more peripheral areas of the macula [14,26]. …”
Section: Discussionmentioning
confidence: 99%